Substrate prediction of Ixodes ricinus salivary lipocalins differentially expressed during Borrelia afzelii infection - Valdés, James J; Cabezas-Cruz, Alejandro; Sima, Radek; Butterill, Philip T; Růžek, Daniel; Nuttall, Patricia A (Scientific reports, 2016)
Evolution has provided ticks with an arsenal of bioactive saliva molecules that counteract host defense mechanisms. This salivary pharmacopoeia enables blood-feeding while enabling pathogen transmission. High-throughput sequencing of tick salivary glands has thus become a major focus, revealing large expansion within protein encoding gene families. Among these are lipocalins, ubiquitous barrel-shaped proteins that sequester small, typically hydrophobic molecules. This study was initiated by mining the Ixodes ricinus salivary gland transcriptome for specific, uncharacterized lipocalins: three were identified. Differential expression of these I. ricinus lipocalins during feeding at distinct developmental stages and in response to Borrelia afzelii infection suggests a role in transmission of this Lyme disease spirochete. A phylogenetic analysis using 803 sequences places the three I. ricinus lipocalins with tick lipocalins that sequester monoamines, leukotrienes and fatty acids. Both structural analysis and biophysical simulations generated robust predictions showing these I. ricinus lipocalins have the potential to bind monoamines similar to other tick species previously reported. The multidisciplinary approach employed in this study characterized unique lipocalins that play a role in tick blood-feeding and transmission of the most important tick-borne pathogen in North America and Eurasia.
Keywords: Protein Structure, Tertiary; ligandy; Ixodes; Analysis of Variance; Saliva; Borrelia burgdorferi komplex; Mice; lipokaliny; analýza rozptylu; sliny; lymeská nemoc; Base Sequence; sekvence nukleotidů; Life Cycle Stages; Ligands; vazebná místa; zvířata; Binding Sites; fylogeneze; myši; Disease Vectors; klíště; Lyme Disease; Phylogeny; Borrelia burgdorferi Group; infekce přenášené vektorem; stadia vývoje; terciární struktura proteinů; Lipocalins; Animals